Learning juggling by gradually increasing difficulty vs. learning the complete skill results in different learning patterns - Geller, Noga; Moringen, Alexandra; Friedman, Jason (Frontiers in Psychology, 2023)
Motor learning is central to sports, medicine, and other health professions as it entails learning through practice. To achieve proficiency in a complex motor task, many hours of practice are required. Therefore, finding ways to speed up the learning process is important. This study examines the impact of different training approaches on learning three-ball cascade juggling. Participants were assigned to one of two groups: practicing by gradually increasing difficulty and elements of the juggling movement ("learning in parts") or training on the complete skill from the start ("all-atonce"). Results revealed that although the all-at-once group in the early stages of learning showed greater improvement in performance, the "learning in parts" group managed to catch up, even over a relatively short period of time. The lack of difference in performance between the groups at the end of the training session suggests that the choice of training regime (between all-at-once and learning in parts), at least in the short term, can be selected based on other factors such as the learner's preference, practical considerations, and cognitive style.